Duality and Dynamics of Education in the Transformation of Gender Roles in Modern Society - Sudahri, Sudahri; El-Yunusi, Muhammad Yusron Maulana; Ghozali, Solchan (Journal of Social Science Studies, 2024)
The transformation of gender roles is a characteristic of modern society, with education often considered a key instrument in this process. This academic paper, based on a literature review, aims to analyses how education influences gender equality and changes in social roles. The study was conducted using a qualitative approach with a thematic synthesis method of relevant literature. The findings show that education has a duality: it can reproduce inequality through hidden curricula and biased pedagogical practices, but at the same time has the potential to be a vehicle for transformation when designed critically. Increased participation of women in higher education has encouraged the renegotiation of roles in the family and the labor market, despite being hampered by double burdens and institutional biases such as the motherhood penalty. The success of education as an instrument of change is highly dependent on institutional support factors such as strong political commitment, a supportive legal framework, alliances with social movements, and adequate public infrastructure. This paper concludes that the effectiveness of education in promoting gender equality is not automatic, but rather the result of a configuration of deliberate policy, reflective pedagogical practices, and alignment with broader social transformation. The implications demand a systemic and sustainable managerial approach at all levels of education provision.